Quality Management Principles and Benefits of their Implementation in Central Banks - Radoica Luburić (Journal of Central Banking Theory and Practice, 2015)
This article discusses the principles of quality management and benefits of their implementation in central banks. It is based on new principles of quality management, in particular to: customer focus, leadership, engagement of people, process approach, improvement, evidence-based decision making, and, relationship management. With a view to continuously improving their performance and achieving sustained success, central banks have a realistic opportunity to use these principles in an efficient and effective manner whereby the top management certainly holds the most responsibility. Quality management principles are analysed herein both in their original form and in terms of their implementation in the financial system and its most prominent entity - central bank. The article also incorporates new standard-related terms such as 'context' and 'risk-based thinking' that significantly strengthen quality management principles and contribute to a more effective and efficient achievement of sustainable success.
Keywords: M00; M54; 330; Quality management principles; Customer Focus; Leadership; Engagement of People; Process Approach; Improvement; Evidence-based Decision Making; Relationship Management; benefits; implementation; central banks